Adenylate kinase 4 modulates oxidative stress and stabilizes HIF-1α to drive lung adenocarcinoma metastasis - Jan, Yi-Hua; Lai, Tsung-Ching; Yang, Chih-Jen; Lin, Yuan-Feng; Huang, Ming-Shyan; Hsiao, Michael (Journal of hematology and oncology, 2019)
Adenylate kinase 4 (AK4) has been identified as a biomarker of metastasis in lung cancer. However, the impacts of AK4 on metabolic genes and its translational value for drug repositioning remain unclear. Ingenuity upstream analyses were used to identify potential transcription factors that regulate the AK4 metabolic gene signature. The expression of AK4 and its upstream regulators in lung cancer patients was examined via immunohistochemistry. Pharmacological and gene knockdown/overexpression approaches were used to investigate the interplay between AK4 and its upstream regulators during epithelial-to-mesenchymal transition (EMT). Drug candidates that reversed AK4-induced gene expression were identified by querying a connectivity map. Orthotopic xenograft mouse models were established to evaluate the therapeutic efficacy of drug candidates for metastatic lung cancer. We found that HIF-1α is activated in the AK4 metabolic gene signature. IHC analysis confirmed this positive correlation, and the combination of both predicts worse survival in lung cancer patients. Overexpression of AK4 exaggerates HIF-1α protein expression by increasing intracellular ROS levels and subsequently induces EMT under hypoxia. Attenuation of ROS production with N-acetylcysteine abolishes AK4-induced invasion potential under hypoxia. Pharmacogenomics analysis of the AK4 gene signature revealed that withaferin-A could suppress the AK4-HIF-1α signaling axis and serve as a potent anti-metastatic agent in lung cancer. Overexpression of AK4 promotes lung cancer metastasis by enhancing HIF-1α stability and EMT under hypoxia. Reversing the AK4 gene signature with withaferin-A may serve as a novel therapeutic strategy to treat metastatic lung cancer.